Enhancing nurses' capacity to provide concurrent mental health and substance use disorder care: A quasi-experimental intervention study. (October 2022) - Jenkins, Emily; Currie, Leanne M.; Hirani, Saima; Garrod, Emma; Goodyear, Trevor; McGuinness, Liza; David, Anita; Bonnie, Kofi
Abstract: Background: Patients experiencing concurrent disorders (i.e., co-occurring mental health and substance use disorders) are prevalent in mental health settings and their health and social outcomes are often poor. This reflects persistent stigma as well as inadequate preparatory training or continuing education for healthcare professionals, including nurses. Objective: To explore the impacts of the 1-day 'Enhancing Concurrent Disorder Care Intervention' on nurses' and student nurses' capacity to deliver care, grounded in current evidence, to patients with concurrent disorders in inpatient mental health settings. Design: A Quasi-experimental intervention design was used with pre- and post t -test components, guided by the STROBE checklist for observational studies. Settings: Five acute mental health units across two hospitals in British Columbia, Canada, as well as two schools of nursing representing students completing clinical practicum rotations within these settings. Participants: Seventy-six nurses (Registered Nurses and Registered Psychiatric Nurses) and student nurses practicing in inpatient mental health care. Methods: This educational intervention was informed by a pilot study, which included content validation from international concurrent disorder experts, and further refined through collaborative processes with lived experience and nurse partners. Intervention impacts were examined using online surveys conducted prior to the intervention and within two weeks post-intervention. Surveys assessed knowledge and attitudes about concurrent disorders using a validated instrument and questions developed by the study team. Descriptive statistics alongside paired and independent t -tests and two-way ANOVAs were used to compare survey scores before and after the intervention. Results: Findings indicate that the intervention was effective in improving participants' knowledge and attitudes toward patients with concurrent disorders across participant groups. Conclusions: Enhancing care and outcomes for patients with concurrent disorders is a global priority. Brief educational interventions aimed at nurses can provide an effective, low-barrier mechanism to address knowledge gaps that contribute to harmful care and adverse outcomes. Highlights: Patients commonly experience concurrent mental health and substance use disorders. Gaps in health professions training impact the quality of concurrent disorder care. This study reports on a nursing education intervention about concurrent disorders. The intervention improved knowledge and attitudes among nurses and student nurses. Brief educational interventions with nurses can enhance concurrent disorder care.